2001
DOI: 10.1074/jbc.m006318200
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Monoxide (NO) and Glucose

Abstract: Nitrogen monoxide (NO) affects cellular iron metabolism due to its high affinity for this metal ion. Indeed, NO has been shown to increase the mRNA binding activity of the iron-regulatory protein 1, which is a major regulator of iron homeostasis. Recently, we have shown that NO generators increase 59 Fe efflux from cells prelabeled with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…We investigated NO-mediated 59 Fe release from cells and found it to be energy-and temperature-dependent (16,17). We also reported that glucose metabolism by the hexose monophosphate shunt (HMPS) stimulated NO-mediated Fe efflux from cells (16,17).…”
Section: Nitrogen Monoxide (No)-mediated Iron Release From Cells Is Lmentioning
confidence: 99%
See 4 more Smart Citations
“…We investigated NO-mediated 59 Fe release from cells and found it to be energy-and temperature-dependent (16,17). We also reported that glucose metabolism by the hexose monophosphate shunt (HMPS) stimulated NO-mediated Fe efflux from cells (16,17).…”
Section: Nitrogen Monoxide (No)-mediated Iron Release From Cells Is Lmentioning
confidence: 99%
“…We also reported that glucose metabolism by the hexose monophosphate shunt (HMPS) stimulated NO-mediated Fe efflux from cells (16,17). Moreover, using the GSH synthesis inhibitor L-buthionine-[S,R]-sulfoximine (BSO), we showed that a product of the HMPS, namely GSH, was essential for NO-mediated Fe release (16)(17)(18). We proposed that NO-mediated Fe efflux occurred as a GSFe-NO complex, which is exported from cells by energy-dependent transport (17).…”
Section: Nitrogen Monoxide (No)-mediated Iron Release From Cells Is Lmentioning
confidence: 99%
See 3 more Smart Citations